2009
DOI: 10.2320/matertrans.m2009201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tellurium Doping on the Thermoelectric Properties of ZnSb

Abstract: N-type tellurium doped ZnSb was prepared by direct melting at 923 K after which it was quenched in water within an evacuated quartz ampoule. All the ingots were heat treated at 723 K for 100 h. The resultant samples were characterized by X-ray diffraction (XRD), differential thermal analysis (DTA) and by measurement of their Seebeck and Hall coefficients. XRD and DTA indicated that the solubility limit of tellurium in ZnSb was less than 3 atomic%. The samples with 0, 1 and 3 atomic% tellurium were p-type while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 9 publications
(8 reference statements)
4
17
0
Order By: Relevance
“…4 Melt-growth and powder-metallurgy methods have been used to prepare b-Zn 4 Sb 3 materials. [5][6][7][8][9][10] b-Zn 4 Sb 3 crystals prepared by conventional melt growth contain many cracks that result from thermal stress because of c-to b-phase transformations. Recently, a crack-free single-phase b-Zn 4 Sb 3 material was obtained using direct melting followed by a two-stage heat treatment, also being reported elsewhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Melt-growth and powder-metallurgy methods have been used to prepare b-Zn 4 Sb 3 materials. [5][6][7][8][9][10] b-Zn 4 Sb 3 crystals prepared by conventional melt growth contain many cracks that result from thermal stress because of c-to b-phase transformations. Recently, a crack-free single-phase b-Zn 4 Sb 3 material was obtained using direct melting followed by a two-stage heat treatment, also being reported elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a crack-free single-phase b-Zn 4 Sb 3 material was obtained using direct melting followed by a two-stage heat treatment, also being reported elsewhere. 10 Finely grained powder-metallurgical processes such as mechanical alloying (MA) and mechanical grinding (MG) have been used to obtain homogeneous materials. [11][12][13][14] In general, fine-grain-size materials have lower thermal conductivities than single crystals of the same materials because phonons can be scattered at grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that it is possible to reduce successfully the thermal conductivity of ZnSb by nanostructuring [18,19] and increase its zT up to about 1 [19]. It has also been reported that the n-doped compound with tellurium can have similar electronic properties (and hence zT) to the p-doped material [20] (recent experimental studies have explored other n-type doping but without significant success [21]). These recent results open new perspectives for the orthorhombic ZnSb compound without the stability and doping problems of Zn 4 Sb 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Telkes has investigated the production of solar thermoelectric generators using p-type ZnSb. [2][3][4][5] However, according to reports in the available literature, 9,10) preparation of single-phase ZnSb has proved to be difficult.…”
Section: Introductionmentioning
confidence: 99%